2014
DOI: 10.2319/062314-452.1
|View full text |Cite
|
Sign up to set email alerts
|

Microdamage generation by tapered and cylindrical mini-screw implants after pilot drilling

Abstract: Objective: To investigate the relationship between mini-screw implant (MSI) diameter (1.6 vs 2.0 mm) and shape (tapered vs cylindrical) and the amount of microdamage generated during insertion. Materials and Methods: Thirty-six cylindrical and 36 tapered MSIs, 6 mm long, were used in this study. Half of each shape was 1.6 mm in diameter, while the other half was 2.0 mm. After pilot drilling, four and five MSIs were inserted, respectively, into fresh cadaveric maxillae and mandibles of dogs. Bone blocks contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…The gross pattern of microcracks showed both concentric and radial alignment, unlike what has been reported in previous studies [ 19 , 29 ]. This discrepancy occurred primarily because the sections were viewed differently.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The gross pattern of microcracks showed both concentric and radial alignment, unlike what has been reported in previous studies [ 19 , 29 ]. This discrepancy occurred primarily because the sections were viewed differently.…”
Section: Discussioncontrasting
confidence: 95%
“…Furthermore, little is known about the repair or healing of microdamage induced by cortical bone screws, dental implants, and MIs. A limited number of studies have performed histomorphometric analysis on the microdamage around MIs; however, most of these studies analyzed microdamage immediately after the installation, evaluated the effects of MI design or different pre-drilling procedures, and mainly dealt with bone-to implant contact [ 7 , 10 , 19 , 27 , 28 ]. In one of these studies, the researches took direct histomorphometric measurements of the microdamage as the healing period progressed and found that four weeks of healing were necessary for the microdamage to be repaired [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Inflammation of soft tissues around the head of miniimplant is common and may lead to loss of clinical stability. [5][6][7][8][9][10][11] The main action to prevent periimplantitis is mini-implant insertion through firm attached gingiva. 2,15 Other factors related to inflammation are root contact during insertion, orthodontic auxiliaries attachment and oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear evidence is available in this respect. [6][7][8][9][10] Although clinical features and adverse effects of dental implants (e.g. peri-implantitis and pain) have been investigated extensively, lack of sufficient evidence still exists for orthodontic mini-implants.…”
mentioning
confidence: 99%